The Analysis of Fe3O4/Graphene Oxide Magnetic Properties Synthesized from Corn Cobs Waste as A Potensial Material for Chemotherapy Agents - Aziz, Abdul; Darvina, Yenni; Ratnawulan, Ratnawulan; Hidayat, Rahmat (Journal of Experimental and Applied Physics, 2024)
Cancer is a medical condition caused by mutations in cellular DNA that damage tissue cell function. The high prevalence of cancer in Indonesia needs to be observed with preventive treatments, one of them by applying nanomedicine for targeted drug delivery at cancer sites. It’s specifically will potential to increase the efficacy of treatment and reduce the side effects. Fe3O4/Graphene Oxide (GO) nanocomposite has been widely studied as an efficient nanocarrier drug delivery for chemotherapeutic agents. Therefore, it’s necessary to research the effect of using Fe3O4/GO as an alternative material in chemotherapy agent development. Variations in the composition of Fe3O4 and GO used can determine the ability of magnetic properties. This study aims to analyze the magnetic properties of Fe3O4/GO nanocomposites from corn cob waste by using the modified hummer method. The results of the study were identified using Vibrating Sample Magnetometer with composition variations of 20%:80%, 30%:70% and 40%:60%. Based on the hysteresis curve it was shown an increase in magnetic properties along with the amount of Fe3O4 in the mixture of Fe3O4/GO nanocomposite, with Saturation Magnetization (Ms) values of 18.2 emu/gram (20%: 80%), 23.2 emu/gram (30%:70%), and 31.1 emu/gram (40%:60%); Remanent Magnetization (Mr) values of 6.82 emu/gram (20%:80%), 8.86 emu/gram (30%:70%), and 12.3 emu/gram (40%:60%) and Intrinsic Coercivity (Hc) values of 0.0421 T (20%:80%), 0.0399 T (30%:70%), and 0.0424 (40%:60%). Based on these characteristics, this sample classified as superparamagnetic material, it can be used as an alternative material of nanocarrier drug delivery for chemotherapeutic agents.